Effects Of Trade Liberalization On Economic Growth And Balance Of Payment Of ASEAN Five Plus Three - Yong, Chen Chen (2007)

(untitled)
ASEAN -5 plus 3 ( Malaysia, Thailand, Philippines, Singapore, Indonesia, Japan, Korea and China) have undergone a substantial trade liberalization in the mid 1980s. As a result, the share of exports in GDP has also risen as the region became more industrialized. A greater reliance on exports has helped the region to sustain rapid growth rate but at the same time it has made the region more dependent upon import demand from the rest of the world particularly the industrial countries. These countries were running huge surpluses in 2000 and 2001, compared with large deficits just a few years earlier. Indeed, it is assumed that the initial export growth and trade surplus generates such favourable responses in the economy that the balance of payments surplus actually grows. There is no consideration given to the possibility that the rate of growth of income determined by the rate of growth of imports and thereby imposing a constraint on the export-led growth rate. In addition, there is a fairly well defined and trade-off showing that the faster the rate of growth of output, the worse the trade balance in the balance of payments; and conversely, as growth slowed the deficit improved and a surplus developed. Thus we should analyze whether the economic growth is constrained by the trade balance in the balance of payments. Panel analysis is employed to estimate the effect of trade liberalization on export growth, import growth and the balance of payments for ASEAN-5 plus 3 based on Thrilwall’s Law for a sample period of 1970-2003. This study finds that liberalization stimulated export growth but raised import growth by more for Japan, Malaysia and Korea. Among all, Indonesia is found to be constrained by the external market. In conclusion, the findings have important implications for the sequencing and degree of liberalization.